PEKERJA SEKS KOMESIAL TERSELUBUNG (STUDI KASUS KOST PSK TERSELUBUNG DI PERUMAHAN JONDUL LAMA KECAMATAN TENAYAN RAYA PEKANBARU) - Rudi Teguh Handoyo; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research was conducted in the Old Jondul Housing located in the Village District of Sari Rejo Tenayan Kingdom Pekanbaru is located not far from the former Localization Teleju the first disbanded by the government. Based on the report of the Social Service Pekanbaru City on March 22 s / d 5 April 2010 recorded approximately 412 people and 178 people pimp prostitutes in Localization Teleju Pekanbaru. This study aims to determine the effects of the presence of prostitution to the community around the area of prostitution and describe the role of reciprocity between prostitutes disguised with a boarding house owner PSK veiled settled. The theory used in this study is the structural-functional theory and the theory of the role. This study uses qualitative research methods deskripstif. Data collection techniques in this research is to use the method of direct observation in the Old Jondul housing located in District fifty Pekanbaru with snowball sampling technique. Researchers do this observation to obtain a complete and detailed data about people, time, place, situation and condition. Some things that were observed in this study, among others, about the circumstances of a boarding house of prostitution, and sex workers in residential veiled Old Jondul Pekanbaru. The results of this study indicate that their presence in the area of housing is very disturbing residents and cause bad impacts for residents Housing residents who until now could only surrender and submit this issue all the apparatus-related law enforcement. The function of the role of reciprocity between prostitutes disguised by the owner of the boarding house where prostitutes disguised settled. Where is this relationship raises a cooperative relationship between the prostitute and the owner Kost and between the two can be mutually beneficial and protect the space for prostitution that occurs. Keywords: Sex, Prostitutes, Covert